Supervised internship in children education: a dialectical relationship Between theory and practice (Olhar de Professor, 2020)
This paper presents the legislation on supervised internship and theoretical references about itsimportance in undergraduate courses, specifically in the Children Education, it is different from the other stages,considering the age served (0 to 5 years), because has as characteristic the discovery of the world through play,playfulness, interaction with peers, objects and their most experienced partners. Historically, this stage has beenlinked to care, often dissociated to educational actions. We present a experience report of a partnership for internshipbetween an institution of public Children Education and a teacher training institute of high school, in the Normalmodality in Curitiba-PR. The dialectical movement between theory and practice provided by the internship shownew perspectives to the initial and continuous teachers’ training.
Keywords: Children Education. Supervised internship. Teacher Training.